Business Groups in Korea: Overall Concentration, Market Dominance and Diversification - Jaehyung Lee (Korea Development Institute (KDI), 2014)
- This study attempts a statistical examination and analysis of the characteristics and situation surrounding business groups (Chaebol) in Korea in order to provide basic information for corporation policy and the ongoing business group debate. - Business groups have continued to account for an overwhelming share of the Korean economy, even after the intense restructuring of the late 1990s foreign exchange crisis. - The 55 business groups subject to cross-investment restrictions in 2010 accounted for 29.1 percent of all sales and 8.0 percent of all workers in the national economy. - In terms of broader industry categories, business groups represent an overwhelming portion of manufacturing sector and relatively low percentage of services sector. - As a long-term pattern of change, the top 30 business groups in manufacturing sector have accounted for a rapidly growing share since the late 2000s. This phenomenon is the result of continued rapid growth by a small number of very large companies amid a general drop-off in growth for the economy as a whole. - For manufacturing sector, business groups account for a generally large share of the country's mainstay industries, but not an especially large share of its smaller-scale ones. 󰋫 Business groups have moved into a wide range of industries and frequently hold monopoly or oligopoly status in those markets. - For industries where large business groups ranked among the top three performing companies, the average concentration rate for the three companies (CR3) was 51.8 percent. ·For industries where large business groups were not present, the CR3 averaged 43.9 percent. - Business groups typically have strong market control in large-scale industries or industries with large markets. · Numerically, business group affiliates ranked first for market share in 23.7 percent of cases, but accounted for 48.5 percent of industry sales.
Keywords: 330